Analysis of Energy Consumption and Performance Test on Rice Planting Using Rice Transplanter : A Case Study in West Sumatera Province, Indonesia - Renny Eka Putri; Rizka Fadhilah; Dinah Cherie; Azkiya Wahyu Novianda (Politeknik Pertanian Negeri Payakumbuh, 2020)
Energy Consumption in the agricultural sector consists of diesel, gasoline, and kerosene for fuel of agricultural machinery (rice transplanter, tractor, rice milling unit, motor sprayer, and water pump) in the sector. The objectives of this study are to determine the total energy consumption of rice planting and to analyse the performance of rice transplanter during rice planting in West Sumatra, Indonesia. This research was conducted on farmer's rice fields in west Sumatera Indonesia. The results obtained from the performance of a rice transplanter machine include working speed of 0.633 m/s, a theoretical work capacity of 0.274 ha/hour, effective work capacity of 0.222 ha/hour and work efficiency of 80.967%. The detail of energy consumption using a rice transplanter are human energy (9.225 MJ/ha), seed energy (255.413 MJ/ha), fuel energy (93.463 MJ/ha) and engine energy (0.821 MJ/ha), so that the total energy consumption is 358.952 MJ/ha.